Financial Crisis in Developing Countries and Structural Weaknesses of the Financial System. (IMF Working Papers; Working Paper ;, 1989)
This paper examines the generation of financial crises in developing economies and shows that the microeconomic structure of the financial sector is a crucial factor in creating the conditions for a crisis. Structural problems of the financial system in developing countries, including implicit insurance on bank liabilities, limitations of capital markets, and lack of appropriate regulations, are sources of financial fragility. The paper concludes that close supervision of bank loans is needed to eliminate these distortions, and the optimal intervention consists of imposing an adjustable bankruptcy penalty on banking activity or charging a fair insurance premium on bank liabilities.